Design as a social practice - Daniels, H; Tse, HM (Springer, 2018)
In this chapter we present the findings of an investigation into the ways in which the discourses and practices of school design produce educational spaces which influence the discourses and practices of teaching and learning when the building is occupied. This investigation involved the development of a methodology for systematically analysing the relationship of school space to the experiences of students, teachers and parents. It expands notions of post occupancy evaluation (POE) research by exploring how the motives of an educational vision which informed an initial school design, those of the final building and those of the people who occupy that building interact in a way which influences experiences of the end users. In this way we sought to understand more about the extent to which a building regulates or governs the behaviour of those who occupy it. Through our approach to multi-professional pedagogic post occupancy evaluation, we came to the view that a building may be understood as a tool which may be used to facilitate change rather than as an instrument of change.